The Influence of Compensation and Career Development Mediated Through Employee Engagement Toward Turnover Intention of The Permanent Officers Employees at The Head Office of PT Bank Syariah Mandiri - Amiral Emeraldo Zahari; Yetti Supriyati; Budi Santoso (Journal of International Conference Proceedings (JICP), 2020)
Human resources is one of the crucial aspects to achieve the company goals. Turnover intention is a serious problem encountered by the company because it can disrupt the company activities in achieving its goals. Turnover intention is the process or attitude of an employee to consider leaving the current job, and to find alternative employment opportunities in other organizations or companies that are better. The objective of this research was to find out the influence of Compensation and Career Development mediated through Employee Engagement toward Turnover Intention of the permanent officers employees at the Head Office of PT Bank Syariah Mandiri. In this research, the researcher took the samples by using non-probability sampling method with a purposive sampling technique. The samples were the permanent officers of PT. Bank Syariah Mandiri (Head Office) consisted of 291 respondents from the total of 404 permanent officers. The researcher used structural equation model in testing, analyzing the data, and model development. The Data were analyzed by using statistical software tools (LISREL 8.8). The results were: 1) Compensation has a direct negative influence on turnover intention, 2) Career development has a direct negative influence on turnover intention, 3) Compensation has a direct positive influence on employee engagement, 4) Career development has a direct positive influence on employee engagement, 5) Employee engagement has a direct negative influence on turnover intention, 6) Compensation has an indirect negative influence on turnover intention through employee engagement and 7) Career development has an indirect negative influence on turnover intention through employee engagement.